2016
DOI: 10.1016/j.radonc.2015.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life outcomes from a dose-per-fraction escalation trial of hypofractionation in prostate cancer

Abstract: Objective This multi-institutional phase I/II trial explored patient-assessed tolerance of increasingly hypofractionated (HPFX) radiation for low/intermediate risk prostate cancer. Methods 347 patients enrolled from 2002–2010. Three increasing dose-per-fraction schedules of 64.7 Gy/22 fx, 58.08 Gy/16 fx and 51.6 Gy/12 fx were each designed to yield equivalent predicted late toxicity. Three quality of life (QoL) surveys were administered prior to treatment and annually up to 3 years. Results Bowel QoL data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Several studies have indicated that prostate cancer responds well to EBRT delivered in fewer fractions with higher doses (hypofractionation) [ 13 , 14 , 15 ]. Stereotactic body radiation therapy (SBRT), also called stereotactic ablative radiotherapy (SABR), is a technique that can deliver higher doses in hypofractionated regimens and has shown comparable biochemical control and morbidity to standard fractionation schedules in prospective randomized trials [ 13 , 16 ].…”
Section: External Beam Radiation Therapymentioning
confidence: 99%
“…Several studies have indicated that prostate cancer responds well to EBRT delivered in fewer fractions with higher doses (hypofractionation) [ 13 , 14 , 15 ]. Stereotactic body radiation therapy (SBRT), also called stereotactic ablative radiotherapy (SABR), is a technique that can deliver higher doses in hypofractionated regimens and has shown comparable biochemical control and morbidity to standard fractionation schedules in prospective randomized trials [ 13 , 16 ].…”
Section: External Beam Radiation Therapymentioning
confidence: 99%
“…Several dose-escalation studies [1][2][3][4][5] for localized prostate cancer (PCa) have shown advanced biochemical relapse-free (bRFS) rates and also better local control for higher total doses using either conventional (CFRT) or simultaneously integrated boost (SIB) schedules. Recently published results 6,7 show that prostate tumours have different biological properties to other tumour localizations.…”
Section: Introductionmentioning
confidence: 99%